Missa Caput - Ockeghem, Johannes c. 1410-1497; Benthem, Jaap van (Utrecht Koninklijke vereniging voor Nederlandse muziekgeschiedenis, 1994)
With preface, editorial principles, abbreviations; the tenor cantus firmus, sources, literature, editions, selected literature, setting.Additional remarks on the transmission and readings of the Missa Caput.